The protective effect of melatonin on cisplatin nephrotoxicity - (:unkn) unknown (EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2000)
Regarding the mechanisms of cisplatin (CP) nephrotoxicity, several hypotheses have been put forward, among which oxidative stress (including depiction of glutathione and production of lipid peroxide) is noticeable. This investigation elucidates the role of the antioxidant system in CP-induced nephrotoxieity and the nc phroprotection by melatonin. Balb/c mice were injected i.p. with: 1) vehicle control; 2) a single dose of 6.5 mg/kg cisplatin, CP group; 3) melatonin in a dose of 10 mg/kg for 5 days after CP injection, CP-M group; 4) melatonin (10 mg/kg) for 5 days before and after CP injection, M-CP-M group; 5) melatonin in a dose of 10 mg:kg For 5 days, M group. Mice were sacrificed 5 days after CP injection to determine blood urea nitrogen (BUN) and serum creatinine, Renal lipid peroxidation (LF) and glutathione (GSH) levels were evaluated in kidney homogenates. Cisplatin administration resulted in increased LP, BUN and serum creatinine levels and decreased GSH levels, whereas melatonin reversed these effects. Morphological kidney damage was apparent in the CP group. Mentioned degeneration was moderate in the CP-M group, whereas morphological findings of the M-CP-M group implied a well preserved kidney tissue. When M was administered alone, it didn't cause any significant change in biochemical parameters. Both C and M groups exhibited similar biochemical and morphological findings in light and transmission electron microscope observation. In conclusion, the present study suggests that melatonin may be of therapeutic benefit when used with CP. (C) 2000 Editions scientifiques et medicales Elsevier SAS.
Keywords: cisplatin; melatonin; nephrotoxicity; lipid peroxidation; glutathione; INDUCED LIPID-PEROXIDATION; CIS-PLATINUM NEPHROTOXICITY; RENAL CORTICAL SLICES; RAT-KIDNEY; GLUTATHIONE; ANTIOXIDANT; DAMAGE; DRUG; MECHANISM; PREVENTS